The Text Density from the Realization of Taxonomic Relation in English Translation of Surah Al-Baqarah - Siti Isma Sari Lubis (English Education : English Journal for Teaching and Learning, 2020)
This research tried to find out the realization of repetition as one of component of taxonomic relation in the Al-Quran. Then, it was analyzed by using logogenesis partern to find out the text density. This study had been conducted by using qualitative research. The data consist of clauses of Taxonomic Relation that limited to repetition type. The source of the data was taken from surah Al Baqarah in English Quran Translation by Yusuf Ali. The result of study showed the realization of taxonomic relation were realized in logogenetic pattern. From ten most frequent lexicals of repetition, it had found that in surah Al Baqarah, medium is the most dominant. It happened because there were some clausea that contain about certain lexical has function to track the discussion in the previous clause as the warning, command and prohibition. Therefore it was concluded that repetition that realized in Surah Al Baqarah make the text in the level moderate until easy to be understood by reader because the frequency of repetition is dense.